Fasciitis by Lactococcus garvieae on an immunosuppressed patient by Diabetes Mellitus - Gustavo Adolfo Valencia Mesías; Iliana N. Cano-Calero; Ana Castillo-Soto (Microbes, Infection and Chemotherapy, 2021)
Lactococcus garvieae, a gram-positive anaerobe facultative coccus, is a well-known pathogen in the aquaculture and cattle sector, being extremely rare for human beings. There are some case reports of infections caused by this microorganism, however, there are no fasciitis cases up to date. This is a case of a 24-year-old patient with uncontrolled diabetes mellitus and previous COVID-19 pneumonia without sequelae, admitted to the emergency room for a case compatible with fasciitis. Three cultures for L. garvieae were obtained from surgical debridement and microbiological studies were performed using automated VITEK-2 equipment. No posterior complications were documented. The patient went through a skin graft with a favorable response without evidence of clinical relapse.